THE LEFT VENTRICLE MYOCARDIAL DEFORMATION IN ARTERIAL HYPERTENSION - Колесник, М.Ю. (World of Medicine and Biology, 2014)
The aim of the study was to determine the features of myocardial deformation of the left ventricle (LV) depending on the parameters of ambulatory blood pressure monitoring (ABPM). The study involved 185 males with uncontrolled hypertension (AH), which were carried out speckle-tracking echocardiography and ABPM. It was found that LV global longitudinal strain has a correlation with average 24-hour levels of blood pressure (BP) and hypertensive load indices. The 24-hour hypertension leads to a reduction of the longitudinal, circumferential and radial LV strain compared to patients with isolated daily hypertension. BP variability and dipping status don’t affect the LV deformation parameters. Pathological morning BP rise is associated with increased radial and circumferential apical LV strain.